Stesichoros's Geryoneis - Curtis, Paul, 1965- (Mnemosyne, Supplements, 2011)
Stesichoros's Geryoneis is without doubt one of the gems of the 6th century. This monograph offers the first full-length commentary (in English) to cover all aspects of the Geryoneis . Included in this monograph is a much-needed revised and up-to-date text together with a full apparatus. As well as concentrating on the poet's usage of metre and language, a particular emphasis has been given to Stesichoros's debt to epic poetry. Innovative too is the proposal that the Geryoneis was closely connected with the cult worship Geryon received in the 6th century. This book has an especial appeal to both those already familiar with lyric and epic poetry, but also, it is hoped, those new to Stesichoros.